Strength Capacity and Body Mass Index Evaluation of Swimmers - da Silva Santos, Thaís Miriã; Shecaira, Tânia Plens; Bueno, Giovanna Carolina; Santos, Henrique de Lima; Gonçalves de Assis, Vinícius; Hirota, Vinicius Barroso; Bernardes, Nathalia (Arena-Journal of Physical Activities, 2021)
Purpose. Muscle strength is an important component of physical ability. In sports such as swimming, this physical capacity has been increasingly evident in training programs, thus becoming important for the performance of aquatic practices. In this context, the aim of this study was to evaluate the strength capacity and the body mass index (BMI) of swimmers. Methods. For this, 20 swimmers of both sexes with a mean age of 38 ± 2 years were evaluated. The handgrip strength (HS) was assessed using a dynamometer and weight and height for calculating BMI. Results. There were no differences in BMI be- tween genders (men (M): 25±1 kg./cm2; women (W): 24±0.9.kg./cm2. Men had a higher HS (M: 42±2; W: 29 ± 2 kgf.) There was no correlation between the HS and the BMI of the swimmers (M: r: 0.44; p: 0.19; W: r: 0.34, p: 0.30). However, the behavior of the relation of the variables differs between the sexes, in men the HS is higher according to a lower BMI, and in women, the HS is higher according to a higher BMI. referring to HS (M: 8.0±0.2; W: 8.4±0.6). Conclusions. Thus, the results of the present study show that the handgrip strength in swimmers is greater in males and does not present correlation with BMI, however it is possible to observe a different behavior between HS and BMI between genders, in men the relationship behavior is negative and in women the relationship behavior is positive.